Analisis Preferensi Pakan Drop In Rusa Sambar (Cervus unicolor) dan Rusa Totol (Axis axis) di Penangkaran PT. Gunung Madu Plantations Lampung Tengah - Indriyani, Susi; Dewi, Bainah Sari; Masruri, Niskan Walid (Jurnal Sylva Lestari, 2017)
Gunung Madu Plantations (GMP) has built deer sanctuary as a part of conservation effort for sambar deer (Cervus unicolor) and spotted deer (Axis axis), this faunas has suppresed by extinction in its natural habitat which means need to be protected by ex-situ concervation effort. Important to conduct the research with aimed to recognize deer's preference towards its served feeder (drop-in) and its availability. The research conducted in October to November 2015 in GMP's deer sanctuary . The method used in the research palatability test method and direct observation method through 8 tail sambar deer (Cervus unicolor) and 10 tail spotted deer (Axis axis). According to the result, food preference of deer in GMP's Deer Sanctuary were elephant grass (Pennisetum purpureum)25.9 %, sauhen grass (Penicum colonum) 22.25%, rayutan (Hypoestes polythyrsa) 21.87%, lamtoro (Leucaena leucocephala) 21.24% and rice mixture (Oryza sativa) 8.74%. Keywords: Preference, Sambar deer (Cervus unicolor), Spotted deer (Axis axis), Sanctuary